Can MDCT Enhancement Patterns Be Helpful in Differentiating Secretory from Non-Functional Adrenal Adenoma? - Kocic, Svetlana; Vukomanovic, Vladimir; Djukic, Aleksandar; Saponjski, Jovica; Saponjski, Dusan; Aleksic, Vuk; Ignjatovic, Vesna; Vuleta Nedic, Katarina; Markovic, Vladan; Vojinovic, Radisa (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Primary adrenal tumors (AT) are a heterogeneous group of neoplasms due to their functional heterogeneity, which results in the diverse clinical presentation of these tumors. The purpose of this study was to examine cross-sectional imaging characteristics using multi-detector computed tomography (MDCT) to provide insight into the lesion characterization and functional status of these tumors. The radionuclide imaging using Technetium-99m radiolabeled hydrazinonicotinylacid-d-phenylalanyl1-tyrosine3-octreotide (99mTc-HYNIC-TOC), was also used in the diagnostic evaluation of these tumors. Materials and Methods: This cross-sectional study included 50 patients with confirmed diagnoses of AT (21 hormone-secreting and 29 non-functional) at the University Clinical Center, Kragujevac, Serbia, during the 2019–2022 year period. The morphological and dynamic characteristics using MDCT were performed, using qualitative, semi-quantitative, and quantitative analysis. Absolute washout (APW) and relative washout (RPW) values were also calculated. A semi-quantitative analysis of all visual findings with 99mTc-HYNIC-TOC was performed to compare the tumor to non-tumor tracer uptake. Results: A statistically significant difference was found in the MDCT values in the native phase (p < 0.05), the venous phase (p < 0.05), and the delayed phase (p < 0.001) to detect the existence of adrenal tumors. Most of these functional adrenocortical lesions (n = 44) can be differentiated using the delayed phase (p < 0.05), absolute percentage washout (APW) (p < 0.05), and relative percentage washout (RPW) (p < 0.001). Furthermore, 99mTc-HYNIC-TOC could have a high diagnostic yield to detect adrenal tumor existence (p < 0.001). There is a positive correlation between radionuclide imaging scan and APW to detect all AT (p < 0.01) and adrenocortical adenomas as well (p < 0.01). Conclusions: The results can be very helpful in a diagnostic algorithm to quickly and precisely diagnose the expansive processes of the adrenal glands, as well as to learn about the advantages and limitations of the mentioned imaging modalities.